PENGARUH KEPUASAN KERJA AUDITOR, PENGALAMAN DAN PROFESIONALISME TERHADAP KUALITAS AUDIT - Shannen Yucta; Hisar Pangaribuan (JOURNAL SCIENTIFIC OF MANDALIKA (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2022)
This study was conducted to determine the effect of auditor job satisfaction, experience, and professionalism on audit quality in public accounting firms in Jakarta. This study uses primary data in the form of answers from respondents to questionnaire data collection. This study uses a purposive sampling method in determining the sample and 63 samples have met the criteria. This study uses multiple linear regression analysis in the data analysis technique, where the results of this study indicate that the experience and professionalism variables affect audit quality, while the auditor's job satisfaction variable does not affect audit quality.